UV-induced photosensing characteristics of SiC and GaN nanowires. Issue 4 (15th July 2019) - Teker, Kasif; Ali, Yassir A.; Uzun, Ali
Abstract : Purpose: This study aims to investigate photosensing characteristics of SiC and GaN nanowire-based devices through exposure to UV light. The photocurrent transients have been modeled to determine rise and decay process time constants. The 1D-semiconductor nanowires can exhibit higher light sensitivity compared to bulk materials because of their large surface area to volume ratio and the quantum size effects. Design/methodology/approach: Nanowire devices have been fabricated through dielectrophoresis for integrating nanowires onto pre-patterned electrodes (10 nm Ti/ 90 nm Au) with a spacing about 3 µm onto SiO2 /Si (doped) substrate. The photocurrent measurements were carried out under room temperature conditions with UV light of 254 nm wavelength. Findings: SiCNWs yield very short rise and decay time constants of 1.3 and 2.35 s, respectively. This fast response indicates an enhanced surface recombination of photoexcited electron-hole pairs. Conversely, GaNNWs yield longer rise and decay time constants of 10.3 and 15.4 s, respectively. This persistent photocurrent suggests a reduced surface recombination process for the GaNNWs. Originality/value: High selective UV light sensitivity, small size, very short response time, low power consumption and high efficiency are the most important features of nanowire-based devices for new and superior applications in photodetectors, photovoltaics, optical switches, image sensors and biological and chemical sensing.